O Programa Institucional de Bolsas de Iniciação à Docência (PIBID) nas vozes dos bolsistas egressos - Silva, Elizeu Won Ancken da (2021)
The study recalls the main formative actions of the Institutional Program for Scholarship Initiation to Teaching (PIBID), in the voice of the former fellows of the Pedagogy course of the Mato Grosso State University (UNEMAT). It has the general objective of analyzing, from the perceptions of former scholarship students of the PIBID of the Pedagogy Undergraduate Course at UNEMAT, from 2014 to 2018, what are the contributions that the Institutional Program for Scholarship Initiation to Teaching (PIBID) brought to their teaching education. The methodological option is classified as applied research, descriptive type, using as technical procedure the case study of quali-quantitative approach. The locus of the research was the PIBID-UNEMAT Subproject of the Degree Course in Pedagogy of the Mato Grosso State University "Carlos Alberto Reys Maldonado", Juara University Campus. The universe of people involved in the mentioned program between the years 2014 and 2018 were 64 scholars of initiation to teaching, 12 supervisors and 04 area coordinators. The sample used in the research consisted of 08 initiation scholars, 02 supervisors and 02 area coordinators. As instruments of collection we used a structured interview script, a questionnaire, and analysis of the reflective memoirs. The data revealed that the participation of the fellows in the PIBID provided them with experiences and learning for the construction of a more solid base for their later work as educators, allowing them to better face the difficulties and challenges in teaching. The data also show that the objectives of the PIBID Program were achieved, since, according to the respondents, there was an improvement in the pedagogical performance of the teacher, observance of their role as educators in society, as well as an improvement in the quality of initial teacher training, since many of the graduates participating in the study are already inserted in school environments or continuing their studies at the Specialization or Master's level.